Feasibility of measuring left ventricular outflow tract velocity time integral as a predictor for stroke volume in pregnant women in labor - Eissa, Mohamed; Dumitrascu, George; Miller, Elizabeth; Racine, Jennifer; Postnikova, Victoria; Rajaleelan, Wesley; Edwards, Wesley; Talab, Hesham; McIsaac, Daniel (The Ultrasound Journal, 2026)
Background: Pregnancy is a time of significant hemodynamic changes. Maintaining adequate cardiac output (CO) and uteroplacental perfusion is a priority in parturients, for favorable maternal-fetal outcomes. Blood pressure is commonly used as a surrogate for CO, although it may poorly correlate with stroke volume (SV) and CO in some cases. An alternative approach is SV estimation using transthoracic echocardiography (TTE) based on the velocity-time integral (VTI) of the left ventricular outflow tract (LVOT). Although VTI has been validated as a tool to estimate SV and CO in acute care contexts, its feasibility and utility in obstetric anesthesia remain unexplored. Therefore, the objective of this study is to evaluate the feasibility and reproducibility of LVOT VTI measurements in parturients during labor. Methods: Following research ethics board approval, 55 full term pregnant female patients with a singleton pregnancy were recruited. TTE was used to calculate the LVOT VTI for each patient by the same anesthesiologist twice. Feasibility of obtaining the LVOT VTI was evaluated using time for image acquisition and the 3-Point Likert Scale for Imaging Quality. Intraclass correlation coefficients (ICC) were used to estimate intra-rater reliability. Results: LVOT VTI was obtained for all participants on both attempts. Mean time needed to obtain measurements was 63.7 seconds (95%CI 56.5 to 70.8) on the 1st attempt and 44.2 seconds (95%CI 38.7 to 49.8) on the 2nd attempt. Eighty-one (73.6%) images were rated as optimal, 29 (26.3%) were rated as suboptimal. Intra-rater reliability was excellent (ICC was 0.94 (95%CI 0.92 to 0.95). Conclusion: In singleton parturients, LVOT VTI measurements can be routinely obtained in a timely fashion with excellent intra-rater reliability during labor. These results support the feasibility of LVOT VTI to estimate and trend SV.